Qualidade de dados em acervos do patrimônio cultural: uma proposta diagnóstica semiautomática para objetos culturais sob gestão do instituto brasileiro de museus - Coelho Júnior, Abeil (2023)
In recent years, there has been an increase in the digitization and availability of cultural heritage data on the internet. However, the quality of the data is often not taken into consideration, which can hinder indexing, search, and navigation for users in information retrieval systems. The Instituto Brasileiro de Museus uses the Inventário Nacional de Bens Culturais Musealizados for the description and publication of data, but this model is not focused on cataloging for standardized standards and vocabularies. This research uses the Cataloging Cultural Objects guide as a reference to assess the quality of data in museum databases managed by Ibram. The objective of the research is to develop a semi-automatic diagnostic evaluation application that allows for the optimization of data quality in cultural heritage collections. The methodology used was applied, qualitative-quantitative, exploratory, and descriptive research, based on a case study of 22 collections of digital museums. The semiautomatic evaluation was performed using the Python language, using regular expressions, and the results revealed cataloging problems related to the physical characteristics of the object, chronological information, geographic location, and description. Finally, the developed application can be used by different users to evaluate the quality of data in their databases and direct efforts towards preventive and corrective actions.